Deregulation, territorial conflicts and resistance movements: the production of mining in the Brazilian Amazon - Muñoz, Edwin (2013)
The article analyzes the conflicts for deregulation and the struggles for territory produced by the advance of mining in the Brazilian Amazon. To illustrate this process, the case of the multinational Alcoa bauxite mining project in the municipality of Juruti, west of Pará State, is presented. The work examines how the current regimes of access to land for mineral extraction along with environmental laws have provided greater power to companies so they appropriate natural resources and authority to regulatesocial demands. This fact is contrasted with the resistance of local communities which main strategy is the struggle for recognition of collective land rights. It is finally suggested that the subordination of the State to the processes of mining expansion is triggering a process of territorialization of the struggle for land, opening new horizons for political action. The empirical basis of this article corresponds to a field study conducted in rural and urban areas of the municipality of Juruti and surrounding region, in 2012.